Reflective, pragmatic, and reactive decision-making by maternity service providers during the SARS-CoV-2 pandemic health system shock: a qualitative, grounded theory analysis - Sergio A. Silverio; Kaat De Backer; Jeremy M. Brown; Abigail Easter; Nina Khazaezadeh; Daghni Rajasingam; Jane Sandall; Laura A. Magee (BMC Pregnancy and Childbirth, 2023)
Abstract Background Pregnant and postpartum women were identified as having particular vulnerability to severe symptomatology of SARS-CoV-2 infection, so maternity services significantly reconfigured their care provision. We examined the experiences and perceptions of maternity care staff who provided care during the pandemic in South London, United Kingdom – a region of high ethnic diversity with varied levels of social complexity. Methods We conducted a qualitative interview study, as part of a service evaluation between August and November 2020, using in-depth, semi-structured interviews with a range of staff (N = 29) working in maternity services. Data were analysed using Grounded Theory analysis appropriate to cross-disciplinary health research. Analysis & findings Maternity healthcare professionals provided their views, experiences, and perceptions of delivering care during the pandemic. Analysis rendered three emergent themes regarding decision-making during reconfigured maternity service provision, organised into pathways: 1) ‘Reflective decision-making’; 2) ‘Pragmatic decision-making’; and 3) ‘Reactive decision-making’. Whilst pragmatic decision-making was found to disrupt care, reactive-decision-making was perceived to devalue the care offered and provided. Alternatively, reflective decision-making, despite the difficult working conditions of the pandemic, was seen to benefit services, with regards to care of high-quality, sustainability of staff, and innovation within the service. Conclusions Decision-making within maternity care was found to take three forms – where at best changes to services could be innovative, at worst they could cause devaluation in care being delivered, and more often than not, these changes were disruptive. With regard to positive changes, healthcare providers identified staff empowerment, flexible working patterns (both for themselves and collectively as teams), personalised care delivery, and change-making in general, as key areas to capitalise on current and ongoing innovations borne out of the pandemic. Key learnings included a focus on care-related, meaningful listening and engagement of staff at all levels, in order to drive forward high-quality care and avoid care disruption and devaluation.